(untitled) (AmeriQuests, 2017)
Review of: Buying Into the Regime: Grapes and Consumption in Cold War Chile and the United States, Heidi Tinsman. (Durham: Duke University Press, 2014. 363 pp.) ISBN 978-0-8223-5535-9. Price 28.95 The Chicken and the Quetzal: Incommensurate Ontologies and Portable Values in Guatemala’s Cloud Forest, Paul Kockelman. (Durham: Duke University Press, 2016. 190 pp.) ISBN 978-0-8223-6072-8. Price 23.95